2014
DOI: 10.1177/1420326x14526424
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and modelling of human-walking-induced particle resuspension

Abstract: Long-term exposure to airborne particulate matter (PM) indoors can cause adverse health effects to the occupants. Such exposure can be influenced by human-walking-induced particle resuspension (HWIPR). Several factors affecting HWIPR were investigated experimentally. The resuspension rates during walking were calculated based on the mass balance model, and the power law was applied to fit the resuspension rate data. The resuspension rate was further normalized for investigating the effects of various factors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 37 publications
0
27
1
Order By: Relevance
“…WIPR is considered by this work as another resuspension scenario. It has been shown that the variation of resuspension rate with respect to time for WIPR could be reasonably described by a power law function: R(t)=anormalrtbnormalr,where a r depends on the factors such as walking strength, particle surface loading, relative humidity (RH), resuspension area, and flooring material …”
Section: Model Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…WIPR is considered by this work as another resuspension scenario. It has been shown that the variation of resuspension rate with respect to time for WIPR could be reasonably described by a power law function: R(t)=anormalrtbnormalr,where a r depends on the factors such as walking strength, particle surface loading, relative humidity (RH), resuspension area, and flooring material …”
Section: Model Developmentmentioning
confidence: 99%
“…A HEPA filter was installed upon the chamber ventilation and the outdoor airborne particles did not enter the chamber during the measurements. The test dust was seeded onto the carpet to a mass concentration of 20 g/m 2 based on which the number concentrations of 2–3 μm and 4–5 μm particles can be estimated based on the size distribution of test dust and the particle density (2650 kg/m 3 ) . The surface mass concentrations for 2–3 μm and 4–5 μm particles are (20 × 0.13 = 2.6 g/m 2 ) and (20 × 0.2 = 4 g/m 2 ), respectively.…”
Section: Physical Validationmentioning
confidence: 99%
See 3 more Smart Citations